Identification of circRNA-associated ceRNA networks in the longissimus dorsi of yak under different feeding systems - Xiaoming Ma; Xian Guo; La Yongfu; Tong Wang; Pengjia Bao; Min Chu; Xiaoyun Wu; Ping Yan; Chunnian Liang (BMC Veterinary Research, 2024)
Abstract Background Yaks (Bos grunniens), prized for their ability to thrive in high-altitude environments, are indispensable livestock in the plateau region. Modifying their feeding systems holds significant promise for improving their growth and meat quality. Tenderness, a key determinant of yak meat quality and consumer appeal, is demonstrably influenced by dietary regimen. Indoor feeding regimes have been shown to enhance tenderness by lowering shear stress and optimizing pH values. CircRNAs, well-known modulators of circulatory function, also play a crucial role in skeletal muscle development across various animal species. However, their functional significance in yak skeletal muscle remains largely unexplored. Results In this study, we identified a total of 5,534 circRNAs within the longissimus dorsi muscle, and we found 51 differentially expressed circRNAs (20 up-regulated and 31 down-regulated) between the two feeding groups. Constructing a comprehensive ceRNA network illuminated intricate regulatory mechanisms, with PGP and circRNA_0617 converging on bta-miR-2285q, mirrored by KLF15/circRNA_0345/bta-miR-20b and CTSF/circRNA_0348/bta-miR-146a. These findings shed light on the potential of circRNAs to influence yak muscle development and meat quality, offering valuable insights for future research. Conclusions This investigation unraveled a complex interaction network between circRNAs、mRNAs and miRNAs in yak skeletal muscle. We further elucidated the target genes regulated by these target genes within the network, offering valuable insights into the potential regulatory mechanisms governing muscle development and meat quality-related traits in yaks.